Čuječnost kot orodje za spoprijemanje s stresom na delovnem mestu: Tehnika STOP - Černetič, Mihael (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Because of the harmful effects of stress on individuals and organizations, successful regulation of employees' work-related stress is nowadays of great importance. Mindfulness (nonjudgmental, accepting awareness of one's own experience in the present moment) has proven to be an effective tool for coping with stress. Unfortunately, classical mindfulness interventions are relatively time-consuming which reduces the possibilities of their application in the context of a workplace and highlights the need for short but effective mindfulness techniques for the regulation of work stress. The aim of this pilot study was to examine the usefulness and effectiveness of a short mindfulness technique called STOP (which takes only one to two minutes to do) for direct coping with stressful situations at work. Participants were practicing the technique for seven days at stressful situations in the workplace. Quantitative results showed a significant reduction of discomfort in employees after doing the STOP technique as well as the increase of their belief regarding their ability to cope with the stressful situation. In addition, qualitative results shed light more broadly on usability and functioning of the technique in relation to workplace stress. It can thus be concluded that the STOP technique is a useful and potentially quite effective tool for regulation of work-related stress.
Keywords: mindfulness; workplace stress; brief techniques